2007
DOI: 10.1016/j.bbi.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of the CX3CR1/p38 MAPK pathway in spinal microglia for the development of neuropathic pain following nerve injury-induced cleavage of fractalkine

Abstract: Accumulating evidence suggests that microglial cells in the spinal cord play an important role in the development of neuropathic pain. However, it remains largely unknown how glia interact with neurons in the spinal cord after peripheral nerve injury. Recent studies suggest that the chemokine fractalkine may mediate neural/microglial interaction via its sole receptor CX3CR1. We have examined how fractalkine activates microglia in a neuropathic pain condition produced by spinal nerve ligation (SNL). SNL induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
321
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 323 publications
(341 citation statements)
references
References 50 publications
16
321
0
4
Order By: Relevance
“…Fortunately, in last several years, we have seen several potential markers, such as the ATP receptor P2X4 (Tsuda et al, 2003), the chemokine receptors CCR2 (Abbadie et al, 2003) and CX3CR1 Zhuang et al, 2007), as well as Toll-like recepotor-4 (TLR4) (Tanga et al, 2005).…”
Section: Microglia Activation and Proliferation In The Spinal Cord Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, in last several years, we have seen several potential markers, such as the ATP receptor P2X4 (Tsuda et al, 2003), the chemokine receptors CCR2 (Abbadie et al, 2003) and CX3CR1 Zhuang et al, 2007), as well as Toll-like recepotor-4 (TLR4) (Tanga et al, 2005).…”
Section: Microglia Activation and Proliferation In The Spinal Cord Inmentioning
confidence: 99%
“…Nerve injury induces a rapid cleavage of fractalkine from the membrane , which involves a cysteine protease cathepsin S that is expressed in microglia (Clark et al, 2007b). Notably, the fractalkine receptor CX3CR1 is only expressed in spinal microglia and upregulated after nerve injury Zhuang et al, 2007). Intrathecal injection of a CX3CR1 neutralizing antibody has been shown to inhibit neuropathic pain and inflammatory pain (Sun et al, 2007).…”
Section: The Role Of Microglia In Pain Controlmentioning
confidence: 99%
“…Fractalkine is another factor released by neurons of the pain pathway, which has been documented to mediate pathological pain (Clark et al, 2007, Lindia et al, 2005, Milligan et al, 2005c, Zhuang et al, 2007. Fractalkine, first discovered as neurotactin (Pan et al, 1997) is a chemokine, a term which refers to a family of over 50 proteins classically known as chemotactic cytokines (Asensio and Campbell, 1999) that induces leukocyte migration and facilitates inflammation (Thomson and Lotze, 2003).…”
Section: Neuron-to-glia Signals: Fractalkinementioning
confidence: 99%
“…Specifically, nerve injury upregulates several receptors, such as the chemokine receptor CX3CR1 and ATP receptor P2X4 in spinal microglia. Either blocking or deleting these receptors results in decreased neuropathic pain (Tsuda et al, 2003;Verge et al, 2004;Zhuang et al, 2006b). Intrathecal injection of ATP-activated microglia induces mechanical allodynia (a nociceptive response to normally innocuous mechanical stimulation) that requires microglial production of BDNF (Tsuda et al, 2003;Coull et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, studies from different laboratories have demonstrated that p38 mitogen-activated protein kinase (MAPK) is activated in spinal microglia under different chronic pain conditions, and that blocking this kinase attenuates pain hypersensitivity (Table 1 ( Jin et al, 2003;Schafers et al, 2003;Tsuda et al, 2004;Boyle et al, 2006;Hains and Waxman, 2006). A recent study shows that nerve injury-induced cleavage of the chemokine fractalkine results in activation of p38 in spinal microglia via CX3CR1 receptors (Zhuang et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%